The Road Network of the Catalan Pyrenees: Development and Current State - Jaume Font; Rosel Majoral (Promet - Traffic&Transportation, 1970)
In this article we analyse the process of development andthe functional characteristics of the road network in the CatalanPyrenees. The study is divided in three main sections: 1) ananalysis of the geographical factors that have been determinantin the growth of the network; 2) a description of the process ofits regional implementation and 3) its current state, includingan evaluation of the plans now in the process of being implementedand recent improvements and an analysis of the significanceof two major undertakings - the Llobregat Axis and thetunnel of Cadi. Special emphasis is placed throughout the wticleon the concept of network integration Labasse, J. 1971),which we define as the degree of connectivity of the comarcas(provincial subdivisions) of the Catalan Pyrenees and theircentres of population to a general road network.This mticle has drawn on both documentmy and bibliographicsources but is based principally on J. Font's doctoralthesis, which analyses the growth of the Catalan road network.Few geographical studies of the transpmt network of the southemslopes of the Pyrenees have been published, be it in Catalanor Spanish journals. This stands in marked contrast to the attentiondedicated to the subject by French academic publications(Pyrenees, Revue de Geograhie des Pyrenees et duSud-Ouest). This said, howevet; we should not overlook thestudies undettaken in Spain by A. Escalona ( 1888), above allthose carried out in the A rag on Pyrenees. Any other articles describingthe Catalan Pyrenees, though, must be tracked down inindividual chapters of regional monographs, both ancient(Sole Sabaris, L. 1951; Llobet, S., 1947) and modem (L6pezPalomeque, F., 1986).The data sources desctibing the Pyrenees transport networkhave improved considerably in recent years. This is due to thegrowth in number of applied studies sponsored by the variousbodies of public administration following the re-establishmentof democracy in Spain (1977) and the restoration of theGeneralitat, the autonomous Catalan government. Amongthese studies, at the comarcal level, the most outstanding arethe comarcal plans for upland areas (Plans Comarcals deMuntanya), carried out at the instigation of the Generalitat andin which the transport network of the comarcas of the Pyreneesare analysed exhaustively; while at the regional level the mostoutstanding source is the study known as the Pla de Carreteresde Catalunya (Generalitat de Catalunya, 1987)- the Road NetworkPlan for Catalonia. These studies, and others of similar importance (MAB-6 programme; Gurera, J., 1988), offer anenviable level of information about the transport network of thecomarcas of the Pyrenees and their prospects for short-term improvement.